Histamine Released From Skin-Infiltrating Basophils but Not Mast Cells Is Crucial for Acquired Tick Resistance in Mice - Tabakawa, Yuya; Ohta, Takuya; Yoshikawa, Soichiro; Robinson, Elisabeth J.; Yamaji, Kayoko; Ishiwata, Kenji; Kawano, Yohei; Miyake, Kensuke; Yamanishi, Yoshinori; Ohtsu, Hiroshi; Adachi, Takahiro; Watanabe, Naohiro; et al. (Frontiers in Immunology, 2018)
Ticks are blood-feeding arthropods that can transmit pathogens to humans and animals, leading to serious infectious diseases such as Lyme disease. After single or multiple tick infestation, some animal species develop resistance to tick feeding, leading to reduced risk of pathogen transmission. In mice infested with larval Haemaphysalis longicornis ticks, both mast cells and basophils reportedly play key roles in the manifestation of acquired tick resistance (ATR), but it remains ill-defined how they contribute to it. Here, we investigated their products responsible for ATR. Treatment of mice with antihistamine abolished the acquired tick resistance while histamine or histamine H1 receptor agonist reduced tick-feeding even in the 1st infestation. In accordance with these, mice deficient for histamine production showed little or no ATR, indicating the crucial role for histamine in the expression of ATR. Adoptive transfer of mast cells and basophils derived from histamine-sufficient or deficient mice to recipient mice lacking mast cells and basophils, respectively, revealed that histamine produced by basophils but not mast cells is essential for the manifestation of ATR, in contrast to the case of local and systemic anaphylaxis where mast cell-derived histamine is the major player. During the 2nd but not 1st tick infestation, basophils accumulated and made a cluster, surrounding a tick mouthpart, in the epidermis whereas mast cells were scattered and localized mainly in the dermis, more distantly from a tick mouthpart. This appears to explain why basophil-derived histamine is much more effective than mast cell-derived one. Histamine-sufficient, but not -deficient mice showed the thickened epidermis at the 2nd tick-feeding site. Taken together, histamine released from skin-infiltrating basophils rather than skin-resident mast cells plays a crucial role in the manifestation of ATR, perhaps through promotion of epidermal hyperplasia that may inhibit tick feeding.